Anti-resultativity in Latin - Чернюх, Богдан Васильович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The paper examines the semantic domain of anti-resultativity (absence of result) as well as lingual means of its rendering in Latin. It has been made explicit that anti-resultativity denoting unreached or cancelled result is verbalized through grammatical and lexical means. An unsuccessful result can be realized in three directions: temporary cessation of the situation, which does not exclude the possibility of its further continuation (interrupted action); the subject’s attempt to achieve the result (a deliberate action); ending the situation at the point that is as close as possible to the finale. The termination of a situation with its possible continuation and logical ending is expressed solely at the lexical level with the help of phase verbs with termination semantics (desino, desisto, cesso) or circumstantial indices that indicate the absence of a result until a certain moment (nondum). The main role is given to the context. The means of expressing a deliberate but not realized action is the imperfect (so-called imperfectum de conatu), the conative meaning of which arises due to the interaction of the actional semantics of predicates (mainly telic verbs) and context and can be interpreted as pragmatic implicature. Explicitly intended action is also expressed by syntagmas with verbs of the corresponding semantics (conor, tempto + infinitive). Termination of a situation at a critical point close to completion is treated in the article as proximity (partial resultativity). It is implemented exclusively at the lexical level with the help of the adverbs paene and, more rarely, prope. Plusquamperfect is used to express cancelled result. The anti-resultative meanings of the Latin imperfectum, as well as that of plusquamperfectum, are consequences of the pragmatic implicature that arises under the influence of the context and/or under the influence of the communicative situation. In the first case, the lack of result can be considered as an implication of durativity, if there is no information about reaching the final point, but only the situation is advised towards it. The anti-resultative meaning of the plusquamperfectum is due to the inherent time interval of the time frame and the connection to the secondary reference point.